Dampak Tingkat Pendidikan, Persepsi Penyakit, Kualitas Pelayanan, dan Aksesibilitas terhadap Pemanfaatan Layanan Rawat Jalan Penyakit Dalam: Scoping Review - Lita Susanti; Izaak Zoelkarnain Akbar; Neka Erlyani; Fauzie Rahman; Muhammad Abdan Shadiqi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Outpatient healthcare utilization, particularly in internal medicine, plays a crucial role in early diagnosis, continuity of care, and clinical outcomes. However, disparities in the utilization of these services remain a challenge due to multiple interrelated determinants. Objective: This scoping review aimed to map and synthesize the evidence regarding the influence of educational attainment, illness perception, service quality, and accessibility on the utilization of internal medicine outpatient services. Methods: The review followed the Arksey and O'Malley framework and was reported in accordance with the PRISMA-ScR guidelines. A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar for studies published between 2016 and 2026. A total of 16 studies met the inclusion criteria and were analyzed. Results: Most included studies employed quantitative cross-sectional designs, while several used qualitative and mixed-methods approaches. Educational attainment was reported as a significant determinant in 12 studies (71%), accessibility in 14 studies (82%), illness perception in 8 studies (47%), and service quality in 6 studies (35%). A combination of individual, psychological, service-related, and structural factors influenced outpatient service utilization. Educational attainment and accessibility were the most frequently reported determinants, whereas illness perception and service quality played roles in shaping healthcare-seeking behavior and continuity of care. Heterogeneity in study design, measurement approaches, and healthcare system contexts was a major limitation. Conclusion: Outpatient internal medicine service utilization is multidimensional and requires integrated strategies, including enhancing health literacy, strengthening patient-centered service quality, and reducing financial and geographical barriers, to achieve more equitable and effective healthcare delivery.